@maxdancona,
First situation Sally with flashlight aimed upward.
S is change in time for Sally.
J is change in time for John.
D is height of spaceship. L is hypotenuse.
S = D/c
L = (D^2 + (vJ)^2)^.5
J = L/c
D = Sc
L = Jc
J = ((D^2 + (vJ)^2)^.5)/c
J = (((Sc)^2 + (vJ)^2)^.5)/c
J^2 = ((S^2)*(c^2) + (v^2)*(J^2))/c^2
J^2 = S^2 + ((v^2)*(J^2))/c^2
J^2 - ((v^2)*(J^2))/c^2 = S^2
J^2*(1-(v^2/c^2)) = S^2
J^2 = S^2/(1-(v^2/c^2))
Finally....
J = S/((1-(v^2))^.5)
Second situation Sally with flashlight aimed at an angle of 53.13 degrees up and to the left.
It is very simple. Since the situation is exactly reversed replace every S with a J and every J with an S.
S is change in time for Sally.
J is change in time for John.
D is height of spaceship. L is hypotenuse.
J = D/c
L = (D^2 + (vS)^2)^.5
S = L/c
D = Jc
L = Sc
S = ((D^2 + (vS)^2)^.5)/c
S = (((Jc)^2 + (vS)^2)^.5)/c
S^2 = ((J^2)*(c^2) + (v^2)*(S^2))/c^2
S^2 = J^2 + ((v^2)*(S^2))/c^2
S^2 - ((v^2)*(S^2))/c^2 = J^2
S^2*(1-(v^2/c^2)) = J^2
S^2 = J^2/(1-(v^2/c^2))
Finally....
S = J/((1-(v^2))^.5)
Why is this wrong or incorrect?